The Knowledge of Balado Chips Producers on The Use of Dyes in Campago Guguk Bulek Village, Bukittinggi - Hidayati, Fajrina (Health Notions, 2018)
Chemical contamination among others comes from the misuse of food additives such as coloring agents which can cause human health problems. The purpose of this research was to describe the knowledge of balado chips producers on the use of dyes in Campago Guguk Bulek Village of Bukittinggi. Subject in this research was 7 producers of balado chips. Primary data was obtained from dye testing in Baristand Padang and producers knowledge was obtained from interview using questionnaire. Data was processed manually and presented in tabular form and described in narrative form. The results showed that there were 3 samples of balado chips do not use additional dyes and 5 samples using additional dye. All producers of red balado chips used a dye of Amaranth as an additional dye and Fast Green FCF dyes on green balado chips. Most producers (85.71%) had a high knowledge of dyes. There were producers that use dyestuffs so that the need for BPOM socialization and supervision of the producers to provide knowledge and understanding of the use of dye.